2015
DOI: 10.1039/c5ra06231d
|View full text |Cite
|
Sign up to set email alerts
|

A facile template-free synthesis of pH-responsive polyelectrolyte/amorphous TiO2 composite hollow microcapsules for photocatalysis

Abstract: This paper presents a novel, facile method for fabricating pH-responsive inorganic/organic composite microspheres with hollow structures in the absence of a step for the removal of the core. Using polyelectrolyte (hydrogel) hollow microspheres without a need for further calcination and chemical etching, minimally cross-linked poly(methacrylic acid/ethylene glycol dimethacrylate/3-(trimethoxysilyl) propylmethacrylate), poly(MAA/EGDMA/TMSPM) [pMET] microspheres were prepared by a distillationprecipitation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In our previous work, we reported that MB molecules in an aqueous solution were decomposed by the high temperature from a strong UV light. 30 Thus, a weak UV light (16 W) was used to measure the precise photodegradation performance of the photocatalysts. All photocatalyst powders were prepared in the dark with magnetic stirring for 1 h before UV light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we reported that MB molecules in an aqueous solution were decomposed by the high temperature from a strong UV light. 30 Thus, a weak UV light (16 W) was used to measure the precise photodegradation performance of the photocatalysts. All photocatalyst powders were prepared in the dark with magnetic stirring for 1 h before UV light irradiation.…”
Section: Resultsmentioning
confidence: 99%